Predatory Publishing and the Dilemma of the Nigerian Academic (2018)
Publication through the open access model has provided unrestricted global access to the latest scientific findings to anyone who has access to the internet. Although open access publishing was originally promoted because of the ‘public good’ it promises to deliver, concerns are being raised about this mode of publishing because of the emergence of dubious practices by publishers whose primary interest is profit and not the promotion of access to scientific knowledge. Predatory open access publishing is a phenomenon widespread in developing countries. This article summarizes the published literature on predatory open access publishing, discusses its potential impact on scholarship in Nigeria and offers suggestions to address the problem.